MICA Expression Is Regulated by Cell Adhesion and Contact in a FAK/Src-Dependent Manner - Moncayo, Gerald; Lin, Da; McCarthy, Michael T.; Watson, Aleksandra A.; O’Callaghan, Christopher A. (Frontiers in Immunology, 2017)
MICA is a major ligand for the NKG2D immune receptor which plays a key role in activating natural killer cells and cytotoxic T cells. We analyzed NKG2D ligand expression on a range of cell types and could demonstrate that MICA expression levels were closely linked to cellular growth mode. While the expression of other NKG2D ligands was largely independent of cell growth mode, MICA expression was mainly found on cells cultured as adherent cells. In addition, MICA surface expression was reduced through increase in cell-cell contact or loss of cell-matrix adherence. Furthermore, we found that the reduction in MICA expression was modulated by FAK/Src signaling and associated with increased susceptibility to NK cell-mediated killing. While the mechanisms of tumor immune evasion are not fully understood, the reduction of MICA expression following loss of attachment poises a potential way by which metastasizing tumor cells avoid immune detection. The role of FAK/Src in this process indicates a potential therapeutic approach to modulate MICA expression and immune recognition of tumor cells during metastasis.